Vampires In Mythology - Diane Bailey
Long ago, vampires were sometimes used to explain what science could not. Since then, the power of the vampire myth has reached a thrilling realism through the magic of film, television, literature, and popular culture. This book explores the evolution of the vampire, from incubi to Edward Cullen. Spine-tingling photographs and illustrations will engage reluctant and recreational readers alike.